DISCUSSION OF DIRECTIONS FOR THE INNOVATIVE DEVELOPMENT OF MANAGEMENT SYSTEMS USING ARTIFICIAL INTELLIGENCE AND DIGITAL TECHNOLOGIES (Eureka Journal of Business, Economics & Innovation Studies, 2026)
This article discusses the main directions for the innovative development of management systems using artificial intelligence (AI) and digital technologies. It analyzes the significance of integrating AI and digital solutions in modern management, highlighting their role in enhancing efficiency and optimizing decision-making processes. The paper examines key trends such as intelligent automation, data-driven management, and the creation of adaptive systems. Furthermore, it addresses the challenges and opportunities arising from the implementation of these technologies, along with strategies for overcoming them. The findings aim to assist organizations in improving competitiveness amidst digital transformation.
Keywords: Artificial Intelligence, Digital Technologies, Management Systems, Innovative Development, Digital Transformation, Decision Making, Automation, Data-Driven Management.